DgF og dansk folkeviseforskning - Jensen, Niels Martin (Danish Yearbook of Musicology, 1979)
1976 was the year of completion for the standard edition of Danish Balladry, Old Popular Ballads of Denmark (Danmarks gamle Folkeviser = DgF). In that year the last two volumes were published, XI: The Tunes and XII: Index Volume both with part of the text in English), and 123 years had gone since Svend Grundtvig began the project with the first instalment of volume I (Legendary Ballads). Giving as its point of departure a brief survey of the scholarly tradition of four generations associated with DgF the article proceeds to a review of DgF XI and XII. While the index volume fulfills the intentions of Grundtvig's first plan (1847) for the scholarly apparatus of the complete edition, DgF XI, containing some 780 tunes for 186 text-types, raises a great many problems as a critieal edition of the Danish ballad tunes. The volume has turned out to be something quite different from what was planned in the 1930s, when the first section appeared in its first edition. The theories of Thorkild Knudsen concerning ballad as song, which have to a great extent determined the method of transcribing the tunes, are in my opinion not suitable as a fundament for a source book like DgF XI. The way in which the tunes ar transcribed is an interpretation, not a critieal rendering of the sources. The lack of information concerning the sources, of editorial remarks and critical and historical comments on the single tunes, make the volume very difficult to use, both for scholarly and practical purposes. We are still in need of an edition of Danish ballad tunes which can fulfill these requirements.